High Therapeutic and Esthetic Properties of Extracellular Vesicles Produced from the Stem Cells and Their Spheroids Cultured from Ocular Surgery-Derived Waste Orbicularis Oculi Muscle Tissues - Kyung Min Lim; Ahmed Abdal Dayem; Yujin Choi; Yoonjoo Lee; Jongyub An; Minchan Gil; Soobin Lee; Hee Jeong Kwak; Balachandar Vellingirl; Hyun Jin Shin; Ssang-Goo Cho (MDPI AG, 2021)
Extracellular vesicles (EVs) are paracrine factors that mediate stem cell therapeutics. We aimed at evaluating the possible therapeutic and esthetic applications of EVs prepared from the waste human facial tissue-derived orbicularis oculi muscle stem cells (OOM-SCs). OOM-SCs were isolated from the ocular tissues (from elders and youngsters) after upper eyelid blepharoplasty or epiblepharon surgeries. EVs were prepared from the OOM-SCs (OOM-SC-EVs) and their three-dimensional spheroids. OOM-SCs showed a spindle-like morphology with trilineage differentiation capacity, positive expression of CD105, CD 90, and CD73, and negative expression of CD45 and CD34, and their stem cell properties were compared with other adult mesenchymal stem cells. OOM-SC-EVs showed a high inhibitory effect on melanin synthesis in B16F10 cells by blocking tyrosinase activity. OOM-SC-EVs treatment led to a significant attenuation of senescence-associated changes, a decrease in reactive oxygen species generation, and an upregulation of antioxidant genes. We demonstrated the regeneration activity of OOM-SC-EVs in in vitro wound healing of normal human dermal fibroblasts and upregulation of anti-wrinkle-related genes and confirmed the therapeutic potential of OOM-SC-EVs in the healing of the in vivo wound model. Our study provides promising therapeutic and esthetic applications of OOM-SC-EVs, which can be obtained from the ocular surgery-derived waste human facial tissues.